Convenient Preparation of 18F-Labeled Peptide Probes for Potential Claudin-4 PET Imaging - Lucia Feni; M. Aymen Omrane; Moritz Fischer; Boris D. Zlatopolskiy; Bernd Neumaier; Ines Neundorf (MDPI AG, 2017)
Since pancreatic cancer is often diagnosed in a late state of cancer development, diagnostic opportunities allowing early disease detection are highly sought after. As such, cancer expression of claudin proteins is markedly dysregulated, making it an attractive target for molecular imaging like positron emission tomography (PET). Claudins are a family of transmembrane proteins that have a pivotal role as members of the tight junctions. In particular, claudin-3 and claudin-4 are frequently overexpressed in pancreatic cancer. 18F-Labeled claudin selective peptides would provide access to a novel kind of imaging tools for pancreatic cancer. In this work we describe the synthesis of the first 18F-labeled probes potentially suitable for PET imaging of claudin-4 expression. These probes were prepared using oxime ligation of 5-[18F]fluoro-5-deoxyribose (5-[18F]FDR) to claudin selective peptides. As a proof-of-principle, one of them, 5-[18F]FDR-Clone 27, was isolated in >98% radiochemical purity and in 15% radiochemical yield (EOB) within 98 min, and with a molar activity of 4.0 GBq/μmol (for 30 MBq of tracer). Moreover, we present first biological data for the prepared 5-FDR-conjugates. These tracers could pave the way for an early diagnosis of pancreatic tumor, and thus improve the outcome of anticancer therapy.